Discount curve estimation by monotonizing McCulloch Splines - Holger Dette; Daniel Ziggel (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2006)
In this paper a new and very simple method for monotone estimation of discount curves is proposed. The main idea of this approach is a simple modification of the commonly used (unconstrained) Mc-Culloch Spline. We construct an integrated density estimate from the predicted values of the discount curve. It can be shown that this statistic is an estimate of the inverse of the discount function and the final estimate can easily be obtained by a numerical inversion. The resulting procedure is extremely simple and we have implemented it in Excel and VBA, respectively. The performance is illustrated by three examples, in which the curve was previously estimated with an unconstrained McCulloch Spline.
Keywords: 519